Asymmetric projection of introspection reveals a behavioural and neural mechanism for interindividual social coordination - Kentaro Miyamoto; Caroline Harbison; Shiho Tanaka; Marina Saito; Shuyi Luo; Sara Matsui; Pranav Sankhe; Ali Mahmoodi; Mingming Lin; Nadescha Trudel; Nicholas Shea; Matthew F. S. Rushworth (Nature Communications)
Abstract When we collaborate with others to tackle novel problems, we anticipate how they will perform their part of the task to coordinate behavior effectively. We might estimate how well someone else will perform by extrapolating from estimates of how well we ourselves would perform. This account predicts that our metacognitive model should make accurate predictions when projected onto people as good as, or worse than, us but not on those whose abilities exceed our own. We demonstrate just such a pattern and that it leads to worse coordination when working with people more skilled than ourselves. Metacognitive projection is associated with a specific activity pattern in anterior lateral prefrontal cortex (alPFC47). Manipulation of alPFC47 activity altered metacognitive projection and impaired interpersonal social coordination. By contrast, monitoring of other individuals’ observable performance and outcomes is associated with a distinct pattern of activity in the posterior temporal parietal junction (TPJp).